Preparing Teacher Interns for International Teaching: A Case Study of a Chinese Practicum Program - Gregory R MacKinnon; Robert Shields (Networks: An Online Journal for Teacher Research, 2020)
Acadia University, a small liberal arts institution, has for 15 years, offered a unique practicum experience for its teacher interns enrolled in the preservice Bachelor of Education. Students travel to Shanghai, China for a period of four months to teach English as a Second Language in school classrooms ranging from grades kindergarten to six. This paper describes the preparation of interns and the inherent challenges they face as pedagogues in a distinctly different teaching context. This action research account seeks to used mixed methods to identify areas of improvement in the process of preparing beginning teachers for a career in international teaching.
Keywords: International teaching; teacher education